Lasting values key to a successful strategic direction for Jhaymarts Industries, Inc. - Lopez, Ulysses S.; Soledad, Miguel D.; Durana, Annalee D. (Davao City School of Management, University of the Philippines Mindanao, 2007)
Jhaymarts Industries, Inc. belongs to the Small and Medium Enterprises category of our economy. From humble beginnings in 1992, it has become a pioneer manufacturer of polyethylene (PE) water pipes and systems service provider in Mindanao. In just fifteen years, it has grown 60 times larger than its original size. Total sales performed an average growth of 19% of Php 60.022 million revenues for the past five years (2002-2006) and total assets achieved a 27% average growth valued at average Php 53.945 million per year (2006-2006). Likewise, net income grew by 23% valued at an average Php 931,557.40 per year (2002-2006). Jhaymarts? is deeply committed to their lasting corporate values, namely: superior quality, customized service and integrity. However, the company experienced a downtrend both sales and profit for the past two years (2005-2006) while the total assets remains to be slightly higher during the same period. The decline could be attributed to be following: 1. The cutthroat pricing strategies practiced by competitive brands by lowering their low-priced products by as much as 35% compared with the Jhaymarts? quality products. These competitive products are usually of lesser quality. 2. The entry of substitutes in the form of class ?B? competitive brands from competitors including dealers from Manila that offer price difference by as much as 45% vs. Jhaymarts? quality products. 3. The increase in manufacturing costs by as much as 14% (2006) due to high 19% rejection rate of their 14-year old extrusion machines or an average of 13% for the past five years (2002-2006). Though these ?below-quality-rejects? are melted again for re-processing, the costs for re-work have taken its toll on their operational efficiency. The strategic paper was precisely formulated to provide Jhaymarts? the strategic and logical direction to restore the upward trend in profitability and efficiency not only for the next five years but to institutionalized the strategic planning process as a vital tool for the company?s continued efforts for growth, productivity and achievement of the organizations? goals and objectives. After undergoing the strategic direction process, this paper proposes the following broad strategies with Profitability as the over-all objective. 1. To enhance internal efficiencies. 2. To pursue expansion programs. These strategies were brought about by the simple analysis that whenever total sales increase there is also a corresponding increase in the profitability. Enhancing internal efficiencies is a logical with a high rejection rate. Finally, it is hoped that the principles behind this strategic paper will serve as a living inspiration by way of application to their SME?s who play a vital role in the growth, development and economic well being of our country.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, December 2007
Keywords: Strategic plan